1999
DOI: 10.1103/physrevlett.83.4413
|View full text |Cite
|
Sign up to set email alerts
|

Ab InitioCalculation of the Electronic and Optical Excitations in Polythiophene: Effects of Intra- and Interchain Screening

Abstract: We present an ab-initio calculation of the electronic and optical excitations of an isolated polythiophene chain as well as of bulk polythiophene. We use the GW approximation for the electronic self-energy and include excitonic effects by solving the electron-hole Bethe-Salpeter equation. The inclusion of interchain screening in the case of bulk polythiophene drastically reduces both the quasi-particle band gap and the exciton binding energies, but the optical gap is hardly affected. This finding is relevant f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
136
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 157 publications
(146 citation statements)
references
References 24 publications
9
136
1
Order By: Relevance
“…In the present paper, we study the one-particle and two-particle excitations of PT and PPV in a crystalline geometry, replacing the effective dielectric environment in our previous calculations by the actual environment in the crystal. Furthermore, the crucial difference between the present calculations and our earlier work on PT 13,14 is that in the present calculations we do allow for wave-function overlap between adjacent chains.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…In the present paper, we study the one-particle and two-particle excitations of PT and PPV in a crystalline geometry, replacing the effective dielectric environment in our previous calculations by the actual environment in the crystal. Furthermore, the crucial difference between the present calculations and our earlier work on PT 13,14 is that in the present calculations we do allow for wave-function overlap between adjacent chains.…”
Section: Introductionmentioning
confidence: 62%
“…15͒ and 0.6 eV, 16 respectively. We have demonstrated that by embedding a polythiophene chain in a medium with the appropriate frequency-dependent dielectric constants, the exciton binding energy is reduced to 0.76 eV, 13,14 while the optical gap remains virtually unaffected. A similar drastic reduction of the exciton binding energy by interchain screening effects was predicted earlier by Moore and Yaron 17 in polyacetylene, within the semiempirical Pariser-Parr-Pople theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper, 17 hereafter referred to as I, we focused on the differences in excitations between an isolated polythiophene ͑PT͒ chain, see Fig. 1, and crystalline polythiophene.…”
Section: -7͔͒ Binding Energies Have Been Proposedmentioning
confidence: 99%
“…It is well understood that, in general, both semi-empirical (such as AM1) and DFT methods provide reasonable geometries and ZINDO can deliver good UV-visible spectra for such molecular systems [14,15]. Even more accurate TD-DFT approaches are able to tackle complicated electronic features such as exciton binding energy [16,17,18] and double excitations [19]. Furthermore, based on the results of the calculations, absorption an emission spectra can be modeled, for example, for polyenes, oligoarylenes, phenylenevinylenes, and polyfluorenes [10,20,21].…”
Section: Introductionmentioning
confidence: 99%